2019
DOI: 10.3390/economies7030088
|View full text |Cite
|
Sign up to set email alerts
|

Self-Employment in Times of Crisis: The Case of the Spanish Financial Crisis

Abstract: While some researchers have suggested that the self-employment (SE) sector is a haven during a financial crisis, others believe that SE is not necessarily the desired outcome, but an indicator that the labor market is tightening for some groups. Few researchers have compared the SE sector before and after the occurrence of a significant financial crisis, especially in developed countries. This paper analyzes the determinants of entry into self-employment during the 2008 Spanish Crisis. Using data from the Encu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Several studies found that women, racialized groups, migrants, youth, and individuals with lower education are frequently found in both NSE and PE [ 12 , 50 , 51 ]. A study examining the effect of the 2008 crisis in Spain noted that the overall downward trend in self-employment was more pronounced for women [ 52 ]. Other research showed that (i) the prevalence of self-employment is higher for men [ 53 , 54 ], older workers and some immigrant groups [ 54 ], (ii) the reasons for opting for self-employment vary between genders [ 53 , 55 ], and (iii) the opportunities to succeed in entrepreneurial roles are impacted by factors such as gender and race [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that women, racialized groups, migrants, youth, and individuals with lower education are frequently found in both NSE and PE [ 12 , 50 , 51 ]. A study examining the effect of the 2008 crisis in Spain noted that the overall downward trend in self-employment was more pronounced for women [ 52 ]. Other research showed that (i) the prevalence of self-employment is higher for men [ 53 , 54 ], older workers and some immigrant groups [ 54 ], (ii) the reasons for opting for self-employment vary between genders [ 53 , 55 ], and (iii) the opportunities to succeed in entrepreneurial roles are impacted by factors such as gender and race [ 53 ].…”
Section: Introductionmentioning
confidence: 99%